Frozen elephant trunk usage in acute aortic dissection. (September 2021) - Okita, Yutaka
This review discusses the clinical applications of the frozen elephant trunk procedure for patients with acute aortic dissection. Sub-analysis of the multicenter Japanese Frozenix study, J-ORCHESTRA, are presented, and recent reports of frozen elephant trunk usage for acute aortic dissection are discussed.